2007
DOI: 10.1016/j.jfms.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of feline immunodeficiency virus infection in domesticated and feral cats in eastern Australia

Abstract: Serum samples from 340 pet cats presented to three inner city clinics in Sydney Australia, 68 feral cats from two separate colonies in Sydney, and 329 cattery-confined pedigree and domestic cats in eastern Australia, were collected over a 2-year period and tested for antibodies directed against feline immunodeficiency virus (FIV) using immunomigration (Agen FIV Rapid Immunomigration test) and enzyme-linked immunosorbent assay methods (Snap Combo feline leukaemia virus antigen/FIV antibody test kit, IDEXX Labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 15 publications
9
77
4
1
Order By: Relevance
“…As has been emphasised recently in a study of renal disease in Australian cats (White et al 2005), the male: female ratio in 'normal cats' must be considered when looking for gender associations in specific diseases. Conditions previously documented to have a male preponderance, such as FIV infection (Norris et al 2007, Gabor et al 2001, lymphosarcoma (Gabor et al 1998), nocardiosis , feline infectious peritonitis (Norris et al 2005) and cryptococcosis (O'Brien et al 2003) would be even more likely to be strongly linked with male gender considering the data for normal cats presented here.…”
Section: Age Gender and Reproductive Status Of Owned Catsmentioning
confidence: 61%
See 2 more Smart Citations
“…As has been emphasised recently in a study of renal disease in Australian cats (White et al 2005), the male: female ratio in 'normal cats' must be considered when looking for gender associations in specific diseases. Conditions previously documented to have a male preponderance, such as FIV infection (Norris et al 2007, Gabor et al 2001, lymphosarcoma (Gabor et al 1998), nocardiosis , feline infectious peritonitis (Norris et al 2005) and cryptococcosis (O'Brien et al 2003) would be even more likely to be strongly linked with male gender considering the data for normal cats presented here.…”
Section: Age Gender and Reproductive Status Of Owned Catsmentioning
confidence: 61%
“…Many published surveys of disease concerning Australian cats quote reference hospital populations that comprise 30%, or even 46% pedigree cats (Norris et al 2007), rather than the 23.4% recorded in this survey. This is potentially because owners of purebred cats are more likely to seek veterinary attention and especially referral to specialist centres compared to "moggies".…”
Section: Breed Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have found an increased incidence of FeLV and FIV infection in cats with cryptococcosis compared with the prevalence in the hospital population [43], with seropositivity for FeLV and FIV being associated with less favourable outcomes [68]. Australian studies [36,44], in contrast, have found that the prevalence of FIV infection in cats with cryptococcosis was not significantly different from a population of ''sick'' cats from the same area, and further studies of FIV seroprevalence have supported this contention [70]. Furthermore, it was found that many cats with concurrent FIV had comparable CD4 counts to cats with cryptococcosis [71], could be successfully treated and did not relapse when therapy was discontinued [37].…”
Section: Cryptococcosis In Catsmentioning
confidence: 89%
“…However, using molecular methods, this prevalence decreases to 4 to 2% of the worldwide cat population (Hayward et al, 2007). This variation is due to population density, reproductive status, age, gender and living conditions, in particular the frequency of street visitation and reproductive disputes (Norris et al, 2007). In Brazil, FIV has been detected through serological research and PCR, in domiciled and straydomestic cats, in São Paulo, Rio de Janeiro, Rio Grande do Sul and Minas Geraisstates, with a prevalence that varied between 2 and 37.5% for FIV and 8 to 63% for FeLV (Caldas et al, 2000;Souza et al, 2002;Caxito et al, 2006;Almeida et al, 2004).…”
Section: Introductionmentioning
confidence: 99%